2021
DOI: 10.1007/s10648-020-09587-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multimedia Pedagogical Agents Predicted by Diverse Theories: a Meta-Analysis

Abstract: Multimedia pedagogical agents are on-screen characters that allow users to navigate or learn in multimedia environments. Several agents' characteristics may moderate their instructional effectiveness, including appearance, gender, nonverbal communication, motion, and voice. Here, we conducted a meta-analysis to test hypotheses from diverse theories predicting the effects of these agents' characteristics. We tested predictions of cognitive load theory, cognitive theory of multimedia learning, computers are soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 99 publications
3
44
1
2
Order By: Relevance
“…Future work is needed in the area to examine why this may occur, and if the results found in this study are replicable in different contexts. It is also worth examining if the presence of the virtual human may have any interaction with the effectiveness of the different narrative styles, since the mere presence of a visually-present agent can influence learning (Castro-Alonso et al, 2021; Schroeder et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work is needed in the area to examine why this may occur, and if the results found in this study are replicable in different contexts. It is also worth examining if the presence of the virtual human may have any interaction with the effectiveness of the different narrative styles, since the mere presence of a visually-present agent can influence learning (Castro-Alonso et al, 2021; Schroeder et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These characters can take many forms, but are often broadly referred to as pedagogical agents when they are designed to support the learning process (Sinatra et al, 2021). Meta-analyses have shown that pedagogical agents can aid learning (Castro-Alonso et al, 2021; Schroeder et al, 2013) but critical questions have arisen, such as how to most effectively design pedagogical agents (Heidig & Clarebout, 2011).…”
mentioning
confidence: 99%
“…Pedagogical agents are animated anthropomorphic characters employed in the digital learning environment to convey information and enhance motivation by simulating social interaction with learners (Kim et al, 2007 ; Castro-Alonso et al, 2021 ). There are two propositions of theories to explain how PA affects multimedia learning.…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of an avatar is not necessary to communicate information in a virtual world (information can be provided merely by a voiceover), the use of an avatar may have positive effects on the motivation to learn [36,37]. Indeed, a recent meta-analysis found that learning with avatars was more effective than learning without these agents [38]. The characteristics of the avatar should be considered when designing a virtual grocery store tour as it may influence the client's emotional response or the effectiveness of the program [39].…”
Section: Discussionmentioning
confidence: 99%